Question and answer
An adverse aggregate supply shock could result from: (a) a sharp rise in productivity. (b) a rapid rise in oil prices. (c) a decline in wages. (d) an appreciation of the dollar
(d) an appreciation of the dollar
Expert answered|tinkermei|Points 515|
Question
Asked 4/5/2012 10:59:00 PM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
In the long run, the profits for a monopolistic competitor (in terms of a return on its investment) will be
Weegy: The demand will decrease and average total cost will increase. This means in the long run, a monopolistically competitive firm will make zero economic profit. (More)
Question
Expert Answered
Asked 4/2/2012 1:28:02 AM
0 Answers/Comments
19,714,685 questions answered
Popular Conversations
Solve. -6b = -15
Weegy: -6b = -15 15 - 6b = 0 b = 5/2 User: Fill in the blank with the appropriate number. ____ - 39 = ...
3/1/2015 7:14:02 PM| 3 Answers
-6 + (-2)
Weegy: (-6)^-2 = 1/(-6)^2; = 1/36 User: 2/5*2/5
3/1/2015 7:42:50 PM| 2 Answers
Because the soil was depleted during the time of the Dust Bowl many ...
Weegy: moved westward to coastal states User: How did environmental changes in the Great Plains lead to changes in ...
3/1/2015 8:28:08 PM| 2 Answers
What group tends to define hackers and their activities in terms of ...
Weegy: Grey-hat hackers are those that may or may not do harm
3/1/2015 5:23:28 AM| 1 Answers
Which of the following describes the translation of the graph of y = ...
Weegy: x^2 has a negative coefficient so the parabola is opens downward. x-coordinate = 0/2(-1) = 0 ; since ...
3/1/2015 5:54:00 AM| 1 Answers
What is the solution set of x 2 + 5x - 5 = 0?
Weegy: 0.9(5x + 15) = 2.5 - (x + 3) 4.5x + 13.5 = 2.5 - x - 3; 4.5x + x = 2.5 - 3 - 13.5; 5.5x = -14; x = ...
3/1/2015 6:10:17 AM| 1 Answers
If (x + 1)(x - 3) = 12, then which of the following statements is ...
Weegy: x^2 - x - 12 = 0; (x - 4) (x + 3) = 0; x - 4 = 0; x = 4; x + 3 = 0; x - 3; x = {4, -3}
3/1/2015 6:16:37 AM| 1 Answers
Weegy Stuff
S
L
P
L
P
P
Points 78 [Total 7964]| Ratings 0| Comments 78| Invitations 0|Offline
S
P
C
L
P
L
1
Points 27 [Total 7334]| Ratings 0| Comments 27| Invitations 0|Online
S
1
L
L
Points 18 [Total 7519]| Ratings 0| Comments 18| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
P
P
Points 9 [Total 16924]| Ratings 0| Comments 9| Invitations 0|Offline
S
Points 4 [Total 95]| Ratings 0| Comments 4| Invitations 0|Offline
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.